2015
DOI: 10.1111/head.12729
|View full text |Cite
|
Sign up to set email alerts
|

The Sphenopalatine Ganglion: Anatomy, Pathophysiology, and Therapeutic Targeting in Headache

Abstract: The sphenopalatine ganglion (SPG) has attracted the interest of practitioners treating head and face pain for over a century because of its anatomical connections and role in the trigemino-autonomic reflex. In this review, we discuss the anatomy of the SPG, as well as what is known about its role in the pathophysiology of headache disorders, including cluster headache and migraine. We then address various therapies that target the SPG, including intranasal medication delivery, new SPG blocking catheter devices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
149
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(158 citation statements)
references
References 93 publications
(129 reference statements)
0
149
1
8
Order By: Relevance
“…In a study by Ansari et al [53], 95% of patients with facial pain at the beginning of the study reported significant improvement after the study. The facial pain effect size observed in our study (d = 0.96) was much higher than that estimated from Young et al's data (d = 0.51), likely due to the application of multimodal frequencies (70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80) Hz and 1 MHz) in the AxioSonic system. Our effect size for quality of life measures using the SNOT-22 questionnaire (d = 0.45) was lower than Young et al's paper [40] (d = 0.9).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In a study by Ansari et al [53], 95% of patients with facial pain at the beginning of the study reported significant improvement after the study. The facial pain effect size observed in our study (d = 0.96) was much higher than that estimated from Young et al's data (d = 0.51), likely due to the application of multimodal frequencies (70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80) Hz and 1 MHz) in the AxioSonic system. Our effect size for quality of life measures using the SNOT-22 questionnaire (d = 0.45) was lower than Young et al's paper [40] (d = 0.9).…”
Section: Discussioncontrasting
confidence: 87%
“…The SPG is involved in tissue inflammation, lacrimation, mucus production and other parasympathetic processes [71][72][73][74]. Low frequency neurostimulation (20 Hz, much lower than ultrasound frequencies) of the SPG or the Vidian nerve leads to vasodilation and associated inflammation [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…This results in parasympathetic activation of the meningeal vessels, lacrimal glands, nasal, and pharyngeal mucosa. This signaling pathway is referred to as trigeminal-autonomic reflex [4,9]. The activation of this pathway can cause release of vasoactive peptides, such as acetylcholine, vasoactive intestinal peptide, and nitric oxide, and result in plasma protein extravasation and neurogenic inflammation.…”
Section: Pathophysiology Of the Sphenopalatine Ganglia And Its Role Imentioning
confidence: 99%
“…CH is characterized by unilateral headaches in V 1 distribution that are classically associated with parasympathetic disruption, causing lacrimation, conjunctival injection, nasal congestion, and rhinorrhea. Symptoms of sympathetic disruption can also be present in the form of Horner's triad of ptosis, miosis, and anhidrosis [4,12,13]. Like the cluster headache, PH and HC are strictly unilateral headaches with ipsilateral autonomic features [12].…”
Section: Pathophysiology Of the Sphenopalatine Ganglia And Its Role Imentioning
confidence: 99%
See 1 more Smart Citation